Development of the Physical activity and Your Nutrition for Cancer (PYNC) smartphone app for preventing breast cancer in women - Coughlin, Steven S. (Mhealth, 2017)
BACKGROUND: In the U.S., breast cancer accounts for more cancer deaths in women than any site other than lung cancer. Based upon attributable risks, about 30–35% of breast cancers could potentially be prevented by addressing obesity, physical inactivity, increased alcohol consumption, and carcinogenic exposures such as hormone replacement therapy (HRT). We need methods of reducing women’s risks of this disease that are attractive and easy to use, widely accessible to diverse women, and able to be easily amended to account for new research. METHODS: The overall objective of this 12-month project is to develop and test a smartphone app to provide women with information about how they can reduce their risk of breast cancer through healthy behaviors such as physical activity, weight management, restricting caloric intake, consuming a healthy diet and proper nutrition, engaging in regular physical activity, and avoiding carcinogenic exposures such as HRT and alcohol. The specific aims are: (I) to develop a smartphone app for breast cancer prevention using a behavioral framework; (II) to ensure interconnectivity with commercially available products (Fitbit device for monitoring physical activity and the LoseIt! smartphone app for monitoring and tracking diet and nutrition); and (III) to ensure that the mHealth intervention is suitable for women with varying levels of health literacy and eHealth literacy. RESULTS: The app, referred to as Physical activity and Your Nutrition for Cancer (PYNC), is being coded on an iOS platform. Users will be able to access the breast cancer prevention app using their smartphone or tablet. The app’s design will ensure interconnectivity with commercially available products for monitoring and tracking physical activity, caloric intake, diet and nutrition. Using the app, it will be feasible for users to connect and sync their Fitbit and LoseIt! accounts so that information collected about physical activity, caloric intake, diet, and nutrition can be conveniently assessed from one portal. The Fitbit device and app provides reminders and allows users to set physical activity goals. Users will be able to access health education information about breast cancer risk-reduction with attractive graphics and visual displays. CONCLUSIONS: Future directions will include testing the efficacy of the mHealth intervention in increasing physical activity, improving diet and nutrition, and weight management through a randomized controlled trial, and widespread dissemination and implementation research.